Nanoparticle‐mediated genome editing in single‐cell embryos via peptide nucleic acids - Rachael Putman; Adele S. Ricciardi; Kelly E. W. Carufe; Elias Quijano; Raman Bahal; Peter M. Glazer; W. Mark Saltzman (Wiley, 2023)
Abstract Through preimplantation genetic diagnosis, genetic diseases can be detected during the early stages of embryogenesis, but effective treatments for many of these disorders are lacking. Gene editing could allow for correction of the underlying mutation during embryogenesis to prevent disease pathogenesis or even provide a cure. Here, we demonstrate that administration of peptide nucleic acids and single‐stranded donor DNA oligonucleotides encapsulated in poly(lactic‐co‐glycolic acid) (PLGA) nanoparticles to single‐cell embryos allows for editing of an eGFP‐beta globin fusion transgene. Blastocysts from treated embryos exhibit high levels of editing (~94%), normal physiological development, normal morphology, and no detected off‐target genomic effects. Treated embryos reimplanted to surrogate moms show normal growth without gross developmental abnormalities and with no identified off‐target effects. Mice from reimplanted embryos consistently show editing, characterized by mosaicism across multiple organs with some organ biopsies showing up to 100% editing. This proof‐of‐concept work demonstrates for the first time the use of peptide nucleic acid (PNA)/DNA nanoparticles as a means to achieve embryonic gene editing.